ChemInform Abstract: Regioselective Synthesis of 4‐Substituted Indoles via C—H Activation: A Ruthenium Catalyzed Novel Directing Group Strategy. Issue 21 (27th May 2014) - Lanke, Veeranjaneyulu; Ramaiah Prabhu, Kandikere
Abstract The highly regioselective functionalization of indoles at C‐4 position is achieved via ruthenium‐catalyzed coupling with various alkenes.